Characterization of the element content in lacustrine ecosystems in Terra Nova Bay, Antarctica - ABOLLINO, Ornella; MALANDRINO, Mery; ZELANO, Isabella; GIACOMINO, AGNESE; BUOSO, Sandro; MENTASTI, Edoardo (2012)
The distribution of a series of elements in lacustrine environments from Terra Nova Bay, Northern Victoria Land, Antarctica, has been examined, in order to gain insight into the natural processes regulating species distribution, and to detect possible present or future local and/or global anthropogenic contamination. Attention was focused on freshwaters, algae, mosses, and lichens (one site only). Lake water composition was found to be influenced by marine spray, lake geographical position and meltwater input. Bioaccumulation of elements by algae was observed. Higher element concentrations in algae than in mosses have been interpreted taking into account this phenomenon. Data processing by chemometric techniques showed correlations between elements and similarities among samples. No evidence of a detectable metal contamination was found in the investigated area.